2016
DOI: 10.1002/psp.2025
|View full text |Cite
|
Sign up to set email alerts
|

Reshaping Migrant Labour Market Geographies: Local Regularisations and the Informal Economy

Abstract: Regularisation remains a strategic site for studying the political economy of migrant socio-economic incorporation. Research suggests that immigrant regularisation policies improve labour market opportunities for undocumented migrant workers in host societiesparticularly those engaged in the informal economy. However, research on regularisation remains focused on nationallevel policy efforts, despite increased political activity by sub-national levels of government on immigration issues across migrant-receivin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(33 citation statements)
references
References 35 publications
0
33
0
Order By: Relevance
“…It is generally understood that there are multiple drivers of population movements to regions that previously have seen little in‐migration, and that the promise of economic opportunity ranks among the most important. Research has also found that the context of reception in NIDs can figure prominently in the adverse incorporation of migrants, especially in areas where employment opportunities are constrained by discrimination or by tight labour markets, where local policy actors are hostile to the interests of recent immigrants, where xenophobia among residents is pervasive, or where the institutional infrastructure necessary for successful immigrant incorporation is underdeveloped (see Glick Schiller & Çağlar, ; Marrow, ; Phillips & Robinson, ; Samers, ; Visser, ). To date, however, the research literature examining patterns of South–South migration only gestures towards these issues, despite evidence that migration between low‐ and middle‐income countries accounts for a substantial share of total global migration (International Organization for Migration, ).…”
Section: Introduction: New Immigrant Destinationsmentioning
confidence: 99%
“…It is generally understood that there are multiple drivers of population movements to regions that previously have seen little in‐migration, and that the promise of economic opportunity ranks among the most important. Research has also found that the context of reception in NIDs can figure prominently in the adverse incorporation of migrants, especially in areas where employment opportunities are constrained by discrimination or by tight labour markets, where local policy actors are hostile to the interests of recent immigrants, where xenophobia among residents is pervasive, or where the institutional infrastructure necessary for successful immigrant incorporation is underdeveloped (see Glick Schiller & Çağlar, ; Marrow, ; Phillips & Robinson, ; Samers, ; Visser, ). To date, however, the research literature examining patterns of South–South migration only gestures towards these issues, despite evidence that migration between low‐ and middle‐income countries accounts for a substantial share of total global migration (International Organization for Migration, ).…”
Section: Introduction: New Immigrant Destinationsmentioning
confidence: 99%
“…However, for many disconnected youth their families are unable to absorb these costs and these young people must turn to social networks and community organizations to obtain resources that ensure their livelihood. The capacity of disconnected youth to access resources, markets, and their reliance on certain types of networks and institutions simultaneously influence their capacity to ensure social reproduction (Visser, ; Visser, , , , ).…”
Section: Resultsmentioning
confidence: 99%
“…However, many of these activities are hidden in the sense that they are not found or included in annual reports or grant applications CBYSOs submit to their funders. CBYSOs throughout the San Joaquin Valley indicate that over 65% of their funding is received from foundations, while just less than 26% comes from government sources, and under 9% from private donations (Visser, , , , ). Heavy reliance on foundation funding is emblematic of the nature of the larger funding scheme of nonprofits in the US, and is part of the reason why much of the work in CBYSOs to support disconnected youth remains hidden.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations